TUNTUTAN KOMPETENSI BAGI APARATUR DALAM PELAYANAN PUBLIK - Endang Wirjatmi Trilestari1 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
Public service delivery has become the main concern of local government policy. It is to bridge the gap between the dynamic change of social capacity demands and the capacity of local government to fulfill them through public services. To meet the general public demands, local governments have to fully equip their apparatus with appropriate competencies. A range of effort directed to improve apparatus competence in the field of public services has become an endless discussion topic among scholars. Although the demand for better competence has been recorded in numerous policy documents, it does not seem that those efforts have been optimal yet. Therefore, various views on the efforts to enhance apparatus competence in delivering services to society are continuously relevant to be discussed.